The development of contextual-based LKPD with Islamic values to improve students' ability to understand mathematical concepts - Asih Karuniawati; Endah Wulantina (AXIOM : Jurnal Pendidikan dan Matematika, 2025)
This research addresses the issue of the perceived lack of attractiveness of the current teaching materials, as well as the students' limited ability to understand mathematical concepts. The aim of this research is to develop contextually based LKPD (Student Worksheets) incorporating Islamic values that are feasible, engaging, and capable of enhancing students' comprehension of mathematical concepts. This study employs a developmental research methodology, specifically using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The data collection instruments utilized in this study comprised expert validation instruments, student response questionnaires, and tests. The findings indicate that the developed LKPD meets the eligibility criteria, with material experts rating it at 80%, media experts at 88%, and religious experts at 92%. Student responses yielded an average score of 92.4%, categorizing the LKPD as "attractive." The calculation of the average N-Gain Score is 0.82, placing it in the high category. Consequently, it can be concluded that the developed LKPD meets the criteria of eligibility and attractiveness, and significantly enhances students' ability to comprehend mathematical concepts.